Emergent Effects of Residential Lighting Choices: Prospects for Energy Savings. (26th March 2015) - Hicks, Andrea L.; Theis, Thomas L.; Zellner, Moira L.
Summary Artificial lighting has allowed the decoupling of human activities from natural daylight hours. Electricity utilized for artificial lighting accounts for 18.8% of U.S. electricity consumption. Compact fluorescent lamp (CFL) and light‐emitting diode (LED) options are more efficient and have longer lifetimes than conventional incandescent bulbs, but the question remains about the actual energy savings likely to be realized through more efficient lighting delivery systems. This uncertainty influences the rate of adoption and use of efficient lighting technology (and thus the extent and time lags of efficiency gains). Once adopted, gains in efficiency can lead to rebound effects that eliminate these gains and, paradoxically, lock society into increased use of energy. In this study, an agent‐based model and complex systems approach is used to understand how available information and perceptions of different lighting options influence adoption and use, and the potential impact of the rebound effect to reduce the energy savings of energy‐efficient lighting options in a residential setting. Individual households and their decisions are modeled to create overall population‐level consumption data. The multifunctionality of LED lighting may cause consumers to use significantly more light, creating the potential for both rebound and backfire to occur. The results indicate that the adoption of CFL and LED lighting will decrease residential energy consumption if consumers continue to use the same amount or slightly more light; however, when an expansion of lit spaces is included or a large increase in lighting usage occurs, energy consumption will increase and, over time, reduce or completely erode energy savings.